Experimental study of a novel superconducting energy conversion/storage device. (1st September 2021) - Li, Wenxin; Yang, Tianhui; Li, Gengyao; Lu, Jianing; Xin, Ying
Highlights: High efficiency, low loss superconducting energy conversion/storage device. Direct conversion of mechanical energy → electrical energy → mechanical energy. Energy storage used for regenerative breaking in urban rail transit systems. Interaction behavior between permanent magnet and closed superconductor coil. Abstract: A motor and a generator are usually needed for converting the forms of energy between mechanical and electrical in some applications. Recently, we have proposed an energy conversion/storage device based on a unique interacting behavior between a permanent magnet and a closed superconducting coil. This device needs neither a power supply nor a motor/generator and is able to complete the conversion from mechanical energy to electrical energy or the energy storing-releasing cycle of mechanical energy → electromagnetic energy → mechanical energy. In principle, the energy conversion efficiency of this kind of device is higher than most existing energy storages. This article introduces the principle and the experimental results of a proof-of-concept prototype of the proposed device. We conducted three categories of tests on the prototype. The first was for testing the energy conversion efficiency. The second was for examining the electrical loss of the superconducting coil. The third was for exploring the delivering capacity of this kind of device. The results of these experiments demonstrate that this device is able to effectively covert mechanical energy to electrical energy with an efficiency ＞ 90%. The conversion efficiency of a mechanical energy → electrical energy → mechanical energy cycle is greater than 80%. Based on the experimental results, we believe that this kind of device is suitable for being applied in vehicle regenerative braking for energy conservation, particularly meaningful for urban rail transportations.